2021
DOI: 10.1186/s13148-021-01198-z
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal metal exposure, cord blood DNA methylation and persistence in childhood: an epigenome-wide association study of 12 metals

Abstract: Background Prenatal exposure to essential and non-essential metals impacts birth and child health, including fetal growth and neurodevelopment. DNA methylation (DNAm) may be involved in pathways linking prenatal metal exposure and health. In the Project Viva cohort, we analyzed the extent to which metals (As, Ba, Cd, Cr, Cs, Cu, Hg, Mg, Mn, Pb, Se, and Zn) measured in maternal erythrocytes were associated with differentially methylated positions (DMPs) and regions (DMRs) in cord blood and teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 98 publications
(94 reference statements)
1
23
0
Order By: Relevance
“…However, it is predominantly determined by inheritance [ 90 ] and pathways involving many genes and transcription factors [ 91 ]; therefore alternations in head circumference characterize many genetic disorders [ 92 , 93 ] and have been extensively studied. As many of the metals included in this study were previously found to act as genetic modifiers [ 94 96 ], suppressing or enhancing fetal expression of genes, it is not unreasonable to assume that interactions between these metals themselves [ 57 ], or with proteins [ 97 ], including transcription factors, could lead to various alterations in newborns’ phenotypes. Recent studies have suggested that metals could also interact with epigenetic processes that may be crucial to intrauterine development [ 98 ], especially in the context of metal mixtures.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is predominantly determined by inheritance [ 90 ] and pathways involving many genes and transcription factors [ 91 ]; therefore alternations in head circumference characterize many genetic disorders [ 92 , 93 ] and have been extensively studied. As many of the metals included in this study were previously found to act as genetic modifiers [ 94 96 ], suppressing or enhancing fetal expression of genes, it is not unreasonable to assume that interactions between these metals themselves [ 57 ], or with proteins [ 97 ], including transcription factors, could lead to various alterations in newborns’ phenotypes. Recent studies have suggested that metals could also interact with epigenetic processes that may be crucial to intrauterine development [ 98 ], especially in the context of metal mixtures.…”
Section: Discussionmentioning
confidence: 99%
“…Possibly due to similar population characteristics, cg05825244 (annotated to EBF4 ) was identified to be significantly associated with copper in an EWAS study of 1,243 Chinese individuals, 79 which was consistent with our results. Other EWAS studies associated with manganese, arsenic and cadmium, which were performed in populations such as American mother–infant pairs, 79 Bangladeshi adults, 80 and American Indian tribes, 20 however, did not reported similar genes. We have additionally performed an additional analysis of KEGG and GO pathway, where significant sites enriched mainly involved diverse cellular functions such as neuronal axons, synapses, and ion channel activities that were crucial in brain homeostasis involved in the ADL disability process.…”
Section: Discussionmentioning
confidence: 88%
“… 50 Fetal development is a susceptible period of rapid epigenetic reprogramming, and both essential and nonessential metal exposure was shown to influence DNA methylation at birth and in childhood. 51 Programming of metabolic-related genes could influence metabolic trajectories, particularly in periods of accelerated growth. 52 We observed the strongest associations in mid-childhood and adolescence, supporting this hypothesis.…”
Section: Discussionmentioning
confidence: 99%